دور الجامعة في ترسيخ وتعزيز الثقافة المقاولاتية لدى الطالب الجامعي - briam, samia (Finance and Business Economies Review, 2018)
In the wake of the critical oil boom known to Algeria in recent times, the Algerian government adopted a strategy based on a series of reforms that would promote the development of thought or the spirit of mukhtalism that targets a society Young people in general and academics in particular because they are qualified for it, but the success of this strategy depends on the maturity of the entrepreneurial thinking in this segment. Where university education is a major center for the development of entrepreneurial skills. The curriculum should focus on encouraging independence, perseverance, self-confidence and other entrepreneurial skills. The university also has an important role in building knowledge about entrepreneurship and teaching the scientific concepts on which it is based. The aim of this paper is to highlight the role of the university in establishing and strengthening the moral culture of the university student